Fazlallah Astarabadi and the Hurufis - Shahzad Bashir (London Oneworld Publications, 2009)
Fazlallah Astarabadi was a 14th-century Islamic religious leader who believed that the world was about to come to an end. This book is the first comprehensive study of Astarabadi''s life and thought and also offer a history of his movement. It emphasizes the diversity of medieval Islam by describing an apocalyptic movement founded on the idea that the cosmos contains embedded secrets that become manifest through extraordinary human beings.
Include Index
Keywords: Hurufis -- Astarabadi, Fazlallah, 1340-1394